2021
DOI: 10.1016/j.ejso.2020.03.211
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery programmes in older patients undergoing hepatopancreatobiliary surgery: what benefits might prehabilitation have?

Abstract: Due to an aging population and the related growing number of less physically fit patients with multiple comorbidities, adequate perioperative care is a new and rapidly developing clinical science that is becoming increasingly important. This narrative review focuses on enhanced recovery after surgery (ERAS®) programmes and the growing interest in prehabilitation programmes to improve patient-and treatment-related outcomes in older patients undergoing hepatopancreatobiliary (HPB) surgery. Future steps required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 84 publications
1
54
0
Order By: Relevance
“…A recently published article argued that multimodal prehabilitation should include exercise, nutrition and psychosocial care (Kamarajah et al 2020 ). The authors consider it a lost opportunity not to include the other known risk factors and suggest that each patient should be screened for the six risk factors as discussed in the present study, which also corresponds to the recommendation of Bongers and colleagues (Bongers et al 2020 ). In addition, our results showed that 53 of the 77 HPB patients (68.8%) needed at least one intervention, and patients with a low literacy had on average significant more risk factors than patients with a normal health literacy.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…A recently published article argued that multimodal prehabilitation should include exercise, nutrition and psychosocial care (Kamarajah et al 2020 ). The authors consider it a lost opportunity not to include the other known risk factors and suggest that each patient should be screened for the six risk factors as discussed in the present study, which also corresponds to the recommendation of Bongers and colleagues (Bongers et al 2020 ). In addition, our results showed that 53 of the 77 HPB patients (68.8%) needed at least one intervention, and patients with a low literacy had on average significant more risk factors than patients with a normal health literacy.…”
Section: Discussionsupporting
confidence: 69%
“…Although the evidence to support this practice is not yet conclusive, it is mounting rapidly. Although prehabilitation does not harm anyone, it has been suggested that a prehabilitation programme is most beneficial for high-risk patients (Barberan-Garcia et al 2019 ; Berkel et al 2018 ; Barberan-Garcia et al 2018 ; Bongers et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They believe that an outcome measure in which the impact of a complication is also considered (use of resources, length of hospital stay) better describes this 'resilience' , and should be used to investigate potential benefits from prehabilitation. 9,39,41 As opposed to postoperative complications, results of this review did show more consistent results regarding length of hospital stay, favoring the prehabilitation group. 42 Finally, most studies have small patient groups, and lack a power analysis.…”
Section: Lessons Learned From Included Studiesmentioning
confidence: 55%
“…Thereby, monitoring of training progress was not reported in any study, which is important to motivate responders, timely identify nonresponders, and make necessary personalized program adjustments. 39 Included studies generally did not focus on high-risk patients. 7,9,38 Some studies even excluded some of them due to the inability to perform the proposed physical exercise training program.…”
Section: Lessons Learned From Included Studiesmentioning
confidence: 99%